2018
DOI: 10.1016/j.jsb.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The repeat structure of two paralogous genes, Yersinia ruckeri invasin (yrInv) and a “Y. ruckeri invasin-like molecule”, (yrIlm) sheds light on the evolution of adhesive capacities of a fish pathogen

Abstract: Inverse autotransporters comprise the recently identified type Ve secretion system and are exemplified by intimin from enterohaemorrhagic Escherichia coli and invasin from enteropathogenic Yersiniae. These proteins share a common domain architecture and promote bacterial adhesion to host cells. Here, we identified and characterized two putative inverse autotransporter genes in the fish pathogen Yersinia ruckeri NVH_3758, namely yrInv (for Y. ruckeri invasin) and yrIlm (for Y. ruckeri invasin-like molecule). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 276 publications
(377 reference statements)
1
24
0
Order By: Relevance
“…We proceeded to validate our predictions experimentally by evaluating growth requirements of the predicted auxotrophs. We were able to obtain six E. coli (61)(62)(63)(64), three Yersinia (65), three Salmonella (66,67), three Shigella (68,69), and one Klebsiella (70) strain (Fig. 6).…”
Section: Experimental Validation Of Auxotrophies Highlight Technologicalmentioning
confidence: 99%
“…We proceeded to validate our predictions experimentally by evaluating growth requirements of the predicted auxotrophs. We were able to obtain six E. coli (61)(62)(63)(64), three Yersinia (65), three Salmonella (66,67), three Shigella (68,69), and one Klebsiella (70) strain (Fig. 6).…”
Section: Experimental Validation Of Auxotrophies Highlight Technologicalmentioning
confidence: 99%
“…Mehinto et al (2012) suggested the use of this platform use for de novo sequencing of nonmodel fish species, due to the long reading length. PacBio was also used to improve the sequencing of the genome of an African fish species (Conte and Kocher 2015), to perform the complete sequencing of Piscirickettsia salmonis genome, the major pathogen of farmed salmonid fish (Pulgar et al 2015), the complete sequencing of the fish pathogen Flavobacterium columnare strain C#2 genome (Bartelme et al 2016) and in the evaluation of the adhesive capacities of a fish pathogen (Wrobel et al 2017).…”
Section: Next-generation Sequencing-third Generationmentioning
confidence: 99%
“…We recently identified two genes coding for two IATs in Y. ruckeri , namely yrInv (for Y. ruckeri invasin) and yrIlm (for Y. ruckeri invasin‐like molecule) (Leo et al ., 2015; Wrobel et al ., 2017). Their corresponding proteins are composed of an N‐terminal signal peptide, a short periplasmic region containing a peptidoglycan‐binding LysM minidomain, a translocator domain as well as a large, repetitive passenger domain made of immunoglobulin (Ig)‐like domains, capped by a C‐type lectin domain at the C‐terminus in each case.…”
Section: Introductionmentioning
confidence: 99%
“…YrIlm is composed of a variable number of Ig‐like domains depending on the strain, usually 20, whereas YrInv always contains three Ig‐like domains. The expression of YrInv and YrIlm is regulated by environmental factors such as temperature, osmolarity, iron availability as well as the presence of nutrients (Wrobel et al ., 2017). Many IATs are involved in biofilm formation, such as FdeC, IatC and YeeJ from E. coli , and EtInvA from Edwardsiella tarda (Nesta et al ., 2012; Dong et al ., 2013; Martinez‐Gil et al ., 2017; Goh et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%